Forgetting Lot's wife : on destructive spectatorship - Harries, Martin (Fordham University Press, 2007)
Can looking at disaster and mass death destroy us? Forgetting Lot?s Wife provides a theory and a fragmentary history of destructive spectatorship in the twentieth century. Its subject is the notion that the sight of historical catastrophe can destroy the spectator. The fragments of this history all lead back to the story of Lot?s wife: looking back at the destruction of the cities of Sodom and Gomorrah, she turns into a pillar of salt. This biblical story of punishment and transformation, a nexus of sexuality, sight, and cities, becomes the template for the modern fear that looking back at dis.